USE OF NOXOLOGICAL METHODS IN STUDYING HYGIENIC PROBLEMS OF PRESERVING THE HEALTH OF THE WORKING POPULATION - Iskandarova G. T.; Samigova N. R.; Latipov N. M. (Modern American Journals, 2025)
In modern conditions, the educational process should be aimed at ensuring the safety of life and health, which can be based on the knowledge accumulated by noxological science. The main goal of noxology is to deepen and develop knowledge about the security system in the conditions of the negative influence of the techno- and anthroposphere. In recent years, throughout the world, in connection with industrialization, the introduction of new technological methods, modern technological processes, the increase in production capacity, the construction of new enterprises in many industries, significant changes are occurring in the conditions and nature of work. All this ultimately affects human health and life.
Keywords: Environmental issues, innovations in education, noxology, impact factors, working conditions, hidden damage to health, reduction in life expectancy.